Antioxidant activity of blackberry (Rubus sp.) genotypes from the Southern Region of Brazil - HIRSCH, GABRIELA ELISA; VIZZOTTO, MÁRCIA; ABOY, ANA LUCIA; HENRIQUES, AMÉLIA TEREZINHA; EMANUELLI, TATIANA (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2013)
The antioxidant activity and bioactive compounds of different blackberry fruit genotypes from the major Brazilian producer region (three cultivars and four selections) were evaluated and compared to the Cherokee cultivar. Phenolic and anthocyanic extracts were obtained and evaluated for each fruit genotype. The phenolic extracts of selections 02/96 and 07/001 presented higher antioxidant activity than those of cultivars in most assays. This activity was partially correlated to the higher amount of total phenolics in these samples. Thus, the phenolic compounds are probably the major responsible for the antioxidant activity in the diphenyl-2-picrylhydrazyl radical scavenging assay (DPPH), ferric reducing antioxidant power (FRAP) assay and thiobarbituric acid reactive substances (TBARS) assay. Quercetin seems to be responsible for the antioxidant activity of blackberry phenolic extracts in the β-carotene bleaching assay. Concerning anthocyanic extracts, the selection 02/96 and Cherokee cultivar from harvest 2007 had higher antioxidant activity than the other genotypes in most assays. Anthocyanins appear to be the major responsible for the antioxidant activity of anthocyanic extracts in the DPPH and FRAP assays, although ascorbic acid also contributed to the DPPH antioxidant activity. Selection 02/96 appears to have higher antioxidant activity than the commercial cultivars cultivated in the southern Brazil and appears to be promising for nutritional and health purposes.